Determination of sub-bandage pressures associated with various bandage constructs in horses - Canada, Nathan Chase (Kansas State University, 2016)
Objectives: To quantify sub-bandage pressures associated with various bandage constructs applied to the abdomen, distal limb, carpus, and tarsus. To assess the effect of time and /or post-bandaging manipulations on sub-bandage pressures. Study design: Randomized clinical trial Methods: Each bandage’s sub-bandage pressures were measured with the Picopress® compression measuring system at various time points determined by the study protocol. Nine horses were randomly assigned to a treatment regimen consisting of placement of three abdominal bandage types. Bandages were maintained for 24 hours. 8 horses had two types of distal limb bandages (DLC and DLP) applied and maintained for 24 hours. 8 horses had a DLC bandage applied for 96 hours. 8 horses had both carpal and tarsal bandages applied and pressures monitored after application and post walking. A generalized linear model evaluating associations of pressure with location of the sensor, bandage type, time of measurement, and the potential interaction between all variables was performed (P< 0.05). Results: For abdominal bandages, no time and treatment interactions were observed, and bandage pressures were maintained within each treatment group over the 24 hour period. For distal limb bandages, bandage type, sensor location, and time had a significant effect on sub-bandage pressures. For joint bandages, bandage type, sensor location, and post-bandaging manipulations had significant effects on sub-bandage pressures associated with compression bandages. Ambulation did not have a significant effect sub-bandage pressures generated by the carpal elastic bandages. Conclusions: Abdominal sub-bandage pressures do not significantly decrease over a 24 hour period, but generate low sub-bandage pressures. In contrast, limb bandages apply high sub-bandage pressures, but these pressures degrade over the initial 24 hours.
Keywords: Horse; Bandage; Pressure